Ichnofossils study of paleocene sediment source rock cores from Bintuni basin, West Papua, Eastern Indonesia. (June 2018) - Aswan,; Rudyawan, Alfend; Oo, Thaw Zin
Abstract: Ichnofossils content of Paleocene source rock sediment were examined based on two wells cores from Bintuni Basin, West Papua, Indonesia. The cores are from Paleocene interval of Waripi - Daram Formations and known as the potential source rock sediment interval. This study aims to determine the sea level changes during the depositional of the Waripi - Daram Formations. Representative of 18 ichnogeneras including: Arenicolites, Asterosoma, Chondrites, cryptic bioturbation, Glossifungites, Helminthoida, Nereites, Ophiomorpha rudis, Palaeophycus, Phycosiphon, Planolites, Rosselia, Scolicia, Skolithos, Spirophyton, Teichicnus, Thalassinoides, and Zoophycos . The sea level curve generated from both wells based on ichnofossils association, suggest that there were at least three deepening – shallowing cycles. The cycles generally begins by inner to middle neritic interval that sign by appearance of Ophiomorpha and Chondrites with few Phycosiphon, while the deeper interval of outer neritic, upper bathyal into abyssal usually indicated by Zoophycos, Helminthoida, Nereites, Spirophyton and abundant of Phycosiphon . Sea level curve reconstructions based on the depositional environment suggest that during Paleocene Well-2 was located closer to the land compared to Well-1. Rapid shift in the depositional environment could indicate an initiation of regional uplift in the area caused by a new subduction system to the north of the Basin.